2021
DOI: 10.17221/115/2021-pps
|View full text |Cite
|
Sign up to set email alerts
|

Detection, in silico analysis and molecular diversity of phytoplasmas from solanaceous crops in Turkey

Abstract: Phytoplasma-like symptoms of leaf yellowing and calyx malformation were observed in eggplant (Solanum melongena L.), upward leaves and fruit malformation in pepper (Capsicum annuum L.), and aerial tuber formation in potato (S. tuberosum L.) during the survey performed in the late season (August to September) of 2015 and 2016 in Van province (Turkey). A total of 100 samples were tested by nested-PCR using universal primer pairs to assess the sanitary status of the solanaceous crops and to characterise the phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The occurrence of the phytoplasmas is not new in Turkey since there are earlier and recent reports of some hosts (Sertkaya et al, 2007;Ikten et al, 2014;Gazel et al, 2015;Usta et al, 2017b, Usta et al, 2018bUsta et al, 2020). The results of the present study showed that the symptoms of stunting, yellowing, reddening of pear plant and the flower sterility, malformation, big bud and dwarfing of tomato plants collected were all associated with phytoplasmas.…”
Section: Discussionsupporting
confidence: 60%
“…The occurrence of the phytoplasmas is not new in Turkey since there are earlier and recent reports of some hosts (Sertkaya et al, 2007;Ikten et al, 2014;Gazel et al, 2015;Usta et al, 2017b, Usta et al, 2018bUsta et al, 2020). The results of the present study showed that the symptoms of stunting, yellowing, reddening of pear plant and the flower sterility, malformation, big bud and dwarfing of tomato plants collected were all associated with phytoplasmas.…”
Section: Discussionsupporting
confidence: 60%
“…However, the identified phytoplasmas are different mainly according to their geographic distribution. In detail, phytoplasmas identified in the 16SrI group were detected in Japan, Bangladesh, and India [23][24][25]; in the 16SrII-D in Oman, Egypt, and India [26][27][28][29]; in the 16SrIII-B, -J and -U in Brazil [30,31]; in the 16SrVI-A in Turkey [32]; in the 16SrVI-D in India [28,33]; in the 16SrIX-C in Iran [34]; and the 16SrXII-A in Russia and Turkey [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplasma associated diseases in eggplant are mostly reported in Asian, American and African continents. So far different phytoplasmas are reported in diseased eggplants in particular 16StI from Japan, Bangladesh and India [16][17][18], 16SrII-D from Oman, Egypt and India [19][20][21][22], 16SrIII-B, -J and -U from Brazil [23,24], 16SrVI-A from Turkey [25], 16SrVI-D from India [21,26], 16SrIX-C from Iran [27] and 16SrXII-A from Russia and Turkey [28,29]. In many areas of India there were reports of little leaf disease of brinjal.…”
Section: Discussionmentioning
confidence: 99%